PHYSICAL PARAMETERS AND CHEMICAL COMPOSITION OF COMPONENTS OF THE Am-TYPE BINARY SYSTEM RR LYNCIS - Lyubimkov, L. S.; Rachkovskaya, T. M. (Одеські астрономічні публікації, 2017)
On the basis of technique developed earlier we analysed composite spectra of the eclipsing binary RR Lyncis, which has been classified as Am-star. The following values of effective temperature were found: Teff=8020±200 K for the primary component (the star A) and Teff =7150±300 K for the secondary component (the star B). It was shown that the visual magnitude difference between A and B is Δmv =-1m.2. Using evolutionary tracks of different authors we determined the mass M of every component; mean values are MA=1.95±0.06 M☉ and MB=1.57±0.07 M☉. These "evolutionary" masses are in good accordance with MA and MB values found by Kondo (1976) from an analysis of the radial velocity curves and the light curves. Both components appear to be on the main sequence and they have the age t = (1.1±0.3)•109 years.